The Current State of Knowledge on Magnesium’s Influence on Sleep Health: A Narrative Review - Rachwał, Natalia; Sikora, Katarzyna; Niderla, Natalia; Rzeszutek, Jakub; Grzyb, Weronika; Kurnik, Michał; Jaślikowska, Adrianna; Grzybowska, Dominika; Idzik, Kamil; Kubicki, Adrian (Quality in Sport, 2026)
Background: Sleep is a fundamental biological process essential for physical and mental health. Adequate sleep supports metabolic balance, immune function, cognitive performance, and emotional regulation. Chronic sleep insufficiency, however, is a major health burden. There is accumulating evidence to suggest that low magnesium intake and subclinical magnesium deficiency may be associated with poor sleep quality and an increased risk of insomnia. Aim: The aim of this study was to analyze the mechanisms of magnesium action in the body that may influence our sleep health and summarise the available scientific literature on the subject. Materials and methods: A narrative review was performed using PubMed and Google Scholar databases. In total, 29 publications were included, focusing on systematic reviews, meta-analyses, and randomized controlled trials. Results: The reviewed studies show an association between higher magnesium levels and better sleep efficiency. Clinical trials reported modest improvements in sleep quality among groups that either supplemented or had higher dietary intake of Mg compared to placebo. The limitations of most presented trials include relatively small populations and short durations. Conclusions: The reviewed evidence indicates that low magnesium status is associated with fragmented or nonrestorative sleep, while magnesium supplementation may provide modest improvements in sleep outcomes. Future work should clarify optimal dosages and formulations and identify which populations (e.g. older adults, individuals experiencing stress, or those with inflammatory conditions) benefit the most from Mg supplementation.